Utilization of new technologies in global terror emerging research and opportunities - Stacey, Emily 1984 (Advances in Digital Crime, Forensics, and Cyber Terrorism (ADCFCT) Book Series, 2019)
"This book explores new developments in technological advancements and the progression of terror organizations while also examining non-government activist organizations and their new role in protecting internet freedom and combating cyberterrorism"--